Analisis Bibliometrik : Pemetaan Tren Riset Negosiasi Dalam Humas Digital - Nur anisa; Suriyani Musi; Indah Auliani Idros; Kesya Fitrah Maharani Asniati (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2026)
This study aims to map research trends on negotiation in digital public relations during the period 2015–2025 using bibliometric analysis. Data were collected through the Publish or Perish application (version 8.19) using Scopus as the exclusive source via two stages of structured searching, yielding an initial pool of 200 records. After a systematic selection and cleaning process—comprising deduplication, exclusion of non-article document types, and title-based relevance filtering—a final corpus of 57 peer-reviewed journal articles was obtained. Keyword co-occurrence visualization using VOSviewer (version 1.6.20) identified four thematic clusters: (1) negotiation and conflict management, (2) public relations and strategic communication, (3) social media and digital framing, and (4) dialogue and policy advocacy. Critical findings reveal a very weak connection between the 'social media' and 'negotiation' clusters, visually confirming that the intersection of negotiation and digital platforms remains a wide-open research frontier. This study contributes by identifying this gap and proposing the Smart PR-Equity Model as an integrative conceptual framework linking dialogic negotiation, digital brand equity, and technology-driven communication strategy. Keywords : bibliometrics, digital public relations, negotiation, social media, VOSviewer,